Proc. 27th Annual Conference of the International Group for Lean Construction (IGLC) 2019
DOI: 10.24928/2019/0268
|View full text |Cite
|
Sign up to set email alerts
|

Using TVD Simulation to Improve Collaboration

Abstract: Target Value Design (TVD), a lean approach, has been implemented successfully in the past decade in various countries and its process mandates the collaboration of project participants. However, issues of adapting collaborative practices and the time it takes firsttime users to understand TVD practices have been a challenge in TVD projects. Recently, there has been an increase in the creation, reinvention and use of simulations and serious games to teach TVD and other lean principles to project stakeholders en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Devkar et al (2012) used the same questionnaire for evaluating the effectiveness of a TVD simulation exercise. It was also used by Musa et al (2019) when the TVD simulation was administered to 24 practitioners in Nigeria to test their understanding of TVD. Therefore, for consistency, the authors chose to use the same evaluative questionnaire for their online simulation.…”
Section: Post Simulation Discussionmentioning
confidence: 99%
“…Devkar et al (2012) used the same questionnaire for evaluating the effectiveness of a TVD simulation exercise. It was also used by Musa et al (2019) when the TVD simulation was administered to 24 practitioners in Nigeria to test their understanding of TVD. Therefore, for consistency, the authors chose to use the same evaluative questionnaire for their online simulation.…”
Section: Post Simulation Discussionmentioning
confidence: 99%
“…Studies have shown a low level of innovation, a lack of collaboration, and limited knowledge sharing in the construction industry (Musa et al, 2019, Alashwal et al, 2011, Ahmed et al, 2017, Xue et al 2014. The studies noted that investment in Research and development (R&D) and intangible assets (such as new processes) is low (Egan, 1998) due to uncertain demand for new goods, limited collaboration (Musa et al, 2019, Namadi et al, 2017, and low transfer of technology from academia to industry. However, recently, there has been a strong interest to harness the power of innovation through the adoption of digital/smart technologies in LC community.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples in other contexts are reported in the literature. Russel-Smith et al (2014) discussed the possibility of a Sustainable Target Value Design, aiming to reduce the life cycle impacts, setting targets for environmental indicators tools to evaluate the results and use TVD in green buildings design Additional research on TVD included classroom's layout improvements, using TVD to facilitate the decision-making process (Sahadevan and Varghese, 2019), and simulation games to engage stakeholders in Nigeria's real estate context (Musa et al 2019).…”
Section: Introductionmentioning
confidence: 99%